Wewenang Pemerintah dalam Perlindungan Hukum bagi Orang Atau Badan yang Menyelenggarakan Pembangunan Perumahan dalam Undang-Undang Nomor 1 Tahun 2011 Tentang Perumahan dan Kawasan Permukiman - Dimas Purnayoga Rakayoni; Subekti Subekti; Ernu Widodo (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
That housing and settlement development by private business entities is compatible with the Sustainable Development Goals (SDGs) or can also be called Sustainable Development Goals (SDGs) is a sustainable development agenda initiated and agreed upon by the United Nations. Meanwhile, the construction of houses by individuals or individuals is very inconsistent with the programs or agendas set forth by the national and world governments. Of course, if we examine further, the development carried out by each person is very contrary to